Life stages and northern Algonquian women, 1930--1960: The elders remember - Anderson, Kim (University of Guelph, 2010)
This thesis is an investigation of how life stage roles and responsibilities of women were integral to the health and well-being of northern Algonquian peoples during the twentieth century. Theoretical underpinnings for the work come from Anishinaabek life stage "teachings," which stress that health and well-being are dependent on how well community members fulfill life stage roles and responsibilities. The thesis argues that knowledge about how these stages were experienced historically can help Indigenous peoples to decolonize and construct healthier futures. The content of the work is based on oral history with fourteen northern Algonquian elders from the prairies and Ontario, who shared stories about the girls and women of their childhood communities at mid-century (1930 - 1960). Chapter One introduces the thesis and secondary source material, which included historical and ethnographic literature about Algonquian peoples. Chapter Two covers some of the theoretical considerations involved in oral history and Indigenous historiography. Chapters Three to Six analyze life stages as follows: Conception to Walking; "Walking Out" to Puberty; Puberty to Grandmother Years; and Elder life experiences. The dissertation concludes with considering how Anishinaabek life stage theories fit within Indigenous historiography and how they apply to the experiences of northern Algonquian girls and women at mid century.